The Impact of COVID‐19 on Otolaryngology Community Practice in Massachusetts. (2nd February 2021) - Fan, Timothy; Workman, Alan D.; Miller, Lauren E.; Sakats, Mallory Mason; Rajasekaran, Karthik; Brant, Jason A.; Parasher, Arjun K.; Huckins, David; Aliphas, Avner; Glicksman, Robin; Eskander, Antoine; Glicksman, Jordan T.
Abstract : Objectives: Coronavirus disease 2019 (COVID‐19) significantly affected many health care specialties, including otolaryngology. In response to governmental policy changes, many hospitals and private practices in Massachusetts canceled or postponed nonurgent office visits and elective surgeries. The objective of this study was to quantify the impact of COVID‐19 on the provision and practice trends of otolaryngology services for 10 private practices in Massachusetts. Study Design: Retrospective review. Setting: Multipractice study for community practices in Massachusetts. Methods: Electronic billing records from 10 private otolaryngology practices in Massachusetts were obtained for the first 4 months of 2019 and 2020. Questionnaires from these otolaryngology practices were collected to assess financial and staffing impact of COVID‐19. Results: The local onset of the COVID‐19 pandemic had a significant decrease of 63% of visits in comparison to equivalent weeks in 2019. Virtual visits overtook in‐person visits over time. A greater decline in operating room (OR) procedures than for office procedures was recorded. Ninety percent of practices reduced working hours, and 80% furloughed personnel. Seventy percent of practices applied for the Paycheck Protection Program (PPP). Conclusion: COVID‐19 has had a multifaceted impact on private otolaryngology practices in Massachusetts. A significant decline in provision of otolaryngology services aligned with the Massachusetts government's public health policy changes. The combination of limited personnel and personal protective equipment, as well as suspension of nonessential office visits and surgeries, led to decrease in total office visits and even higher decrease in OR procedures.